Phosphonium‐Ring‐Fused Bicyclic Metallafuran Complexes of Ruthenium and Osmium - Yeung, Chi‐Fung; Chung, Lai‐Hon; Ng, Sze‐Wing; Shek, Hau‐Lam; Tse, Sheung‐Ying; Chan, Siu‐Chung; Tse, Man‐Kit; Yiu, Shek‐Man; Wong, Chun‐Yuen (Chemistry : a European journal, 2019)
Metallafuran complexes with a fused five‐membered phosphonium ring were synthesized from reactions between terminal ynones HC≡C(C=O)R and cis‐[Ru/Os(dppm)2Cl2] (dppm=1,1‐bis(diphenylphosphino)methane). A metal–vinylidene‐involving pathway was found to be an energetically feasible formation mechanism for these complexes. These phosphonium‐containing metallafurans, like many phosphonium‐functionalized drugs, have the ability to induce mitochondrial dysfunction. They also exhibit stronger cytotoxicity against several human cancer cell lines in comparison with their metal precursors and the classic anticancer drug cisplatin. Overall, this work provides structural and mechanistic insights for the rational design of functional metallacycles via activation of alkynes by RuII and OsII centers. Ruthenafuran and osmafuran with a fused five‐membered phosphonium ring can be synthesized from reactions between terminal ynones HC≡C(C=O)R and cis‐[Ru/Os(dppm)2Cl2] (dppm=1,1‐bis(diphenylphosphino)methane, see scheme). The metallafurans are able to induce mitochondrial dysfunction, and exhibit stronger cytotoxicity against several human cancer cell lines in comparison with their metal precursors and the classic anticancer drug cisplatin.